A land-based approach for climate change mitigation in the livestock sector. (10th February 2021) - Chiriacò, Maria Vincenza; Valentini, Riccardo
Abstract: Greenhouse gas (GHG) emissions from agriculture, forestry and other land uses (AFOLU sector) cover the 24% of global emissions, representing the second hot spot in the contribution to climate change after the energy sector. Thus, the land sector plays a crucial role in the context of climate change, being both a contributor to the problem and part of its solution, particularly thanks to the capacity of soils and biomass to sequester atmospheric carbon. The challenge of this paper is to understand the extent to which sustainable land management can be a valuable solution for increasing the mitigation potential of the land sector, particularly at small-scale rural landscape level.The paper presents and tests a land-based approach to be applied at small-scale rural landscape level, aiming at reducing and offsetting GHG emissions from the livestock activities, one of the main sources of GHG emissions of the whole agricultural sector. The proposed land-based approach builds on an ensemble of methodologies, including Geographic Information System (GIS) elaboration, Life Cycle Assessment (LCA) and methodologies from the Intergovernmental Panel on Climate Change (IPCC), that allow estimating livestock GHG emissions and the mitigation potential of sustainable land-use options applied in the same small-scale rural landscape.Results from a case study in Italy show that land-based mitigation options applied at small-scale rural landscape level can reduce and completely offset the GHG livestock emissions of the same area, leading to carbon neutral livestock systems. Thus, this study confirms that the land sector can strongly contribute to climate change mitigation if sustainable land-use options are applied. Highlights: Land-based mitigation options at small-scale landscape level can lead to carbon neutral livestock systems. Land sector can strongly contribute to climate change mitigation if sustainable land-based options are applied. Land-based mitigation options can be applied in the immediate proximity of the livestock GHG emissions source. Land-based climate change mitigation contributes also to a wide range of ecological co-benefits at landscape level.